Controllable Effect of Structural Modification of Sulfonylurea Herbicides on Soil Degradation. Issue 11 (24th October 2016) - Hua, Xuewen; Zhou, Shaa; Chen, Minggui; Wei, Wei; Liu, Ming; Lei, Kang; Zhou, Sha; Li, Yonghong; Wang, Baolei; Li, Zhengming
Abstract: The study of soil degradation behaviors of sulfonylurea herbicides in relation to their different structural attributes is utmost important for us to comprehend the development of new eco‐friendly herbicides. It is postulated that the structural modification of the chemical structures could influence their degradation rates in soil. Nine devised structures were synthesized to study their herbicidal activity as well as their soil degradation behaviors respectively. The novel compoundsI‐3 –I‐7 were characterized by UV, 1 H NMR and 13 C NMR, MS and EA. Bioassays indicated that most of target compounds displayed superior herbicidal activities in comparison with Chlorsulfuron. Soil degradation results further confirmed our previous assumption that the introduction of electron‐donating substituents at 5 th position of the benzene ring distinctly increased their degradation rates, among which dimethylamino and diethylamino groups can adjust the degradation rate to a more favorable status. Abstract : The study of soil degradation behaviors of sulfonylurea herbicides in relation to their different structural attributes is utmost important for us to comprehend the development of new eco‐friendly herbicides. The structure/bioassay/soil degradation tri‐factor relationship obtained in this article further confirmed our previous assumption that the introduction of various substitutes at 5 th position of the benzene ring does influence the soil degradation rates of target compounds where electron‐donating groups distinctly increase their degradation rates. These results will provide new clues to discover ecologically safer and environmentally benign herbicides.